Assessing computer skills in Tanzanian medical students: an elective experience - Melvin Rob; Young Eoin JW; Miranda J Jaime; Coombes John C; Samuel Miriam; Azarmina Pejman (BMC, 2004)
Abstract Background One estimate suggests that by 2010 more than 30% of a physician's time will be spent using information technology tools. The aim of this study is to assess the information and communication technologies (ICT) skills of medical students in Tanzania. We also report a pilot intervention of peer mentoring training in ICT by medical students from the UK tutoring students in Tanzania. Methods Design: Cross sectional study and pilot intervention study. Participants: Fourth year medical students (n = 92) attending Muhimbili University College of Health Sciences, Dar es Salaam, Tanzania. Main outcome measures: Self-reported assessment of competence on ICT-related topics and ability to perform specific ICT tasks. Further information related to frequency of computer use (hours per week), years of computer use, reasons for use and access to computers. Skills at specific tasks were reassessed for 12 students following 4 to 6 hours of peer mentoring training. Results The highest levels of competence in generic ICT areas were for email, Internet and file management. For other skills such as word processing most respondents reported low levels of competence. The abilities to perform specific ICT skills were low - less than 60% of the participants were able to perform the core specific skills assessed. A period of approximately 5 hours of peer mentoring training produced an approximate doubling of competence scores for these skills. Conclusion Our study has found a low level of ability to use ICT facilities among medical students in a leading university in sub-Saharan Africa. A pilot scheme utilising UK elective students to tutor basic skills showed potential. Attention is required to develop interventions that can improve ICT skills, as well as computer access, in order to bridge the digital divide.